1996
DOI: 10.2337/diab.45.9.1217
|View full text |Cite
|
Sign up to set email alerts
|

Phlorizin or Vanadate Treatment Reverses Impaired Expression of Albumin and Hepatocyte Nuclear Factor 1 in Diabetic Rats

Abstract: Diabetes decreases transcription of the albumin gene. The role of hyperglycemia in mediating this suppression of albumin gene activity is unclear. To study the effect of glucose in vivo, we treated diabetic rats with phlorizin or vanadate, two agents that ameliorate hyperglycemia without increasing the levels of circulating insulin. When glucose was normalized in diabetic rats with either agent, the hepatic levels of albumin mRNA became indistinguishable from those in nondiabetic animals. In light of our previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(76 reference statements)
1
7
0
Order By: Relevance
“…An identical protein-binding pattern was obtained with these extracts in a gel retardation assay when the G6P WT oligonucleotide was used as the labeled probe (data not shown). This result is consistent with those of Wong and coworkers (42) who showed that although the abundance of HNF-1 protein, though not mRNA, is decreased in streptozotocin-treated diabetic rats and this represents an effect of hyperglycemia rather than hypoinsulinemia because it is reversible upon phlorizin treatment (43). Although these results suggest that insulin treatment does not modify HNF-1 expression or DNA-binding activity, they do not preclude an action of insulin on the transactivation potential of HNF-1.…”
Section: Resultssupporting
confidence: 93%
“…An identical protein-binding pattern was obtained with these extracts in a gel retardation assay when the G6P WT oligonucleotide was used as the labeled probe (data not shown). This result is consistent with those of Wong and coworkers (42) who showed that although the abundance of HNF-1 protein, though not mRNA, is decreased in streptozotocin-treated diabetic rats and this represents an effect of hyperglycemia rather than hypoinsulinemia because it is reversible upon phlorizin treatment (43). Although these results suggest that insulin treatment does not modify HNF-1 expression or DNA-binding activity, they do not preclude an action of insulin on the transactivation potential of HNF-1.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, vanadate treatment fully normalized the insulin receptor mRNA level, indicating that its in vivo effect on the expression of the insulin receptor gene, as with other genes (4-11), occurs at a pretranslational step. In previous studies, phlorizin treatment of steptozotocininduced diabetic rats has been shown to normalize the altered expression of the liver phosphoenolpyruvate carboxykinase (12), Glut 2 (12) and albumin (10) genes, but, unlike vanadate (8), it did not correct the lowered expression of the pyruvate kinase gene (12). In the present study, vanadate and phlorizin treatments were almost equally effective in their ability to prevent the increase in liver insulin receptor number and insulin receptor mRNA level observed in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments with vanadate (4-11) and, to some extent, phlorizin (10,12), have been shown to reverse the altered expression of a number of hepatic genes in streptozotocin-induced diabetic rats. Here, we have extended these findings to the insulin receptor gene, which is over-expressed in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phlorizin Treatment-Phlorizin was dissolved in 1,2-propanediol (0.2 g/ml) and injected intraperitoneally twice a day at a dose of 0.8 g per kg body weight per day for 2 weeks (19). Sham animals received similar amounts of 1,2-propanediol as phlorizin-treated rats.…”
Section: Methodsmentioning
confidence: 99%